A Comprehensive Dataset on Microbiome Dynamics in Rheumatoid Arthritis from a Large-Scale Cohort Study - Jing Li; Jun Xu; Jiayang Jin; Congmin Xu; Yuzhou Gan; Yifan Wang; Ruiling Feng; Wenqiang Fan; Yingni Li; Xiaozhen Zhao; Yucui Li; Shushi Gong; et al. (Scientific Data)
Abstract Alterations in intestinal microbiota have been identified as a key risk factor in rheumatoid arthritis (RA). This study presents a multidimensional gut microbiota profile from a large cohort of RA patients, stratified by disease stage and treatment regimens, and compared to healthy controls. Our dataset comprises gut microbiota profiles from 2,238 individuals, including 1,034 RA patients (Ascia Pacific RA cohort, APRAC) and 1,204 healthy controls. This dataset is enriched with detailed clinical metadata, including patient profiles, treatment histories, and environmental factors, providing a comprehensive “disease exposome” for RA. By integrating 16S rRNA gene sequencing with demographic, clinical, and environmental data, we offer a valuable resource to explore the complex relationships between gut microbiota and RA progression. This large-scale dataset is expected to be a foundation for collaborative research, advancing our understanding of the microbiome’s systemic effects in RA and other autoimmune diseases and potentially guiding new therapeutic approaches.